The Students’ Ability In Explaining The Tourist’ Objects In Makassar - Anwar, Muh; Saleh, Nurming (Interference: Journal of Language, Literature, and Linguistics, 2021)
The aims of this research were to find out the ttudents’ ability of Germany program of FBS UNM in explaining the tourist’ objects in Makassar, and their difficulties in explaining the tourist’ objects in Makassar. This research was a qualitative and qualitative descriptive method ( max method). Applied descriptive qualitative approach. The subjet of this research were the students of germany program  of  FBS UNM who took the subject of Deustch fűr Tourismus II. This research was conducted on May- September 2012. The result of this research showed that the ability of students of Germany program FBS UNM in explaining the tourist’ objects categorized as satisfied with the percentage of 48, 24%. There were three difficulties faced by the students in explaining the tourism field and lack of practice in speaking with the native speaker.